BS EN IEC 61010-2-040. Safety requirements for electrical equipment for measurement, control, and laboratory use. Part 2-040. Particular requirements for sterilizers and washer-disinfectors used to treat medical materials (4th October 2019) - British Standards Institution,
No abstract available